2021
DOI: 10.1039/d0ra10403e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible-light photodegradation of fluoroquinolone-based antibiotics and E. coli growth inhibition using Ag–TiO2 nanoparticles

Abstract: Ag nanoparticles decorated-TiO2 P25 are a viable alternative for the degradation, through a rutile-mediated mechanism, of fluoroquinolone-based antibiotics under visible light irradiation and, at the same time, for bacteria inactivation in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…The common antibiotics CIP and NFX were chosen as models in this study. As we reported in our former publication, [28] Ag-TiO 2 NPs can degrade CIP and NFX under visible-light irradiation. Therefore, we expected that CIP and NFX could be degraded also by the nanocomposites under visible-light irradiation, thanks to the presence of Ag-TiO 2 NPs in the nanocomposites.…”
Section: Visible-light-driven Photocatalytic Activity Of Fe 3 O 4 /P(...supporting
confidence: 73%
See 1 more Smart Citation
“…The common antibiotics CIP and NFX were chosen as models in this study. As we reported in our former publication, [28] Ag-TiO 2 NPs can degrade CIP and NFX under visible-light irradiation. Therefore, we expected that CIP and NFX could be degraded also by the nanocomposites under visible-light irradiation, thanks to the presence of Ag-TiO 2 NPs in the nanocomposites.…”
Section: Visible-light-driven Photocatalytic Activity Of Fe 3 O 4 /P(...supporting
confidence: 73%
“…The preparation pathway for the proposed Fe 3 O 4 /P(NIPAM-co-MAA)/Ag-TiO 2 nanocomposites is schematically illustrated in Scheme S1, Supporting Information, and involves the combination of magnetic Fe 3 O 4 /P(NIPAM-co-MAA) microspheres, previously reported from Wang et al, [27] and Ag-TiO 2 NPs, as previously reported from Wang et al [28] The details are reported in the Experimental Section. The possible explanation about the interaction between the Fe 3 O 4 /P(NIPAM-co-MAA) microspheres and the Ag-TiO 2 NPs in the nanocomposites is that the carboxylate groups on Fe 3 O 4 /P(NIPAM-co-MAA) microspheres may transfer their acidic hydrogen to the surface of Ag-TiO 2 NPs, forming a bridging hydroxyl group and a chemisorbed methacrylate moiety.…”
Section: Preparation and Characterization Of Fe 3 O 4 /P(nipam-co-maa...mentioning
confidence: 96%
“…23 Wang et al showed 92% CIP degradation could be achieved in 240 min under visible light irradiation by Ag-TiO 2 nanoparticles synthesized via a photochemical method. 24 In a recent work by Li et al, g-Fe 2 O 3 @ZnO core-shell heterostructures synthesized via a hydrothermal sintering and atomic layer deposition method demonstrated the 92.5% photodegradation of CIP in 60 min under simulated light conditions. 25 Chatterjee et al synthesized an iron-copper-based metal-organic framework and reported the 74.48% photocatalytic degradation of CIP.…”
Section: Introductionmentioning
confidence: 97%
“…However, especially in the most commonly used crystalline anatase phase, TiO 2 suffers from the drawback of possessing a large bandgap (~ 3.2 eV) which, in turn, implies the use of UV light irradiation for its activation. Therefore, over the years, several methods, including metal and non-metal doping, decoration with noble metals and combination with binary or ternary selenide nanoparticles, have been investigated to enhance the activity of TiO 2 under visible-light by reducing its bandgap and/or by decreasing its electron–hole pair recombination rate 14 21 . The need to obtain also a product with a vast range of applications exploiting the largest available energy source, i.e.…”
Section: Introductionmentioning
confidence: 99%